2021
DOI: 10.3389/fendo.2021.735954
|View full text |Cite
|
Sign up to set email alerts
|

Dietary Modification for Reproductive Health in Women With Polycystic Ovary Syndrome: A Systematic Review and Meta-Analysis

Abstract: ObjectiveDiet has been reported as the first-line management of polycystic ovary syndrome (PCOS). However, the relationship between diet and fertility in PCOS is still controversial. This meta-analysis aimed to evaluate whether diet could promote reproductive health in women with PCOS while providing evidence-based nutrition advice for clinical practice.MethodsSeven databases, including Cochrane Central Register of Controlled Trials, PubMed, Embase, Web of Science, and some Chinese database, were searched up t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
8
1

Year Published

2022
2022
2024
2024

Publication Types

Select...
8
1
1

Relationship

0
10

Authors

Journals

citations
Cited by 26 publications
(12 citation statements)
references
References 72 publications
0
8
1
Order By: Relevance
“…Metformin administration, [60][61][62][63] bariatric surgery, 64 and lifestyle modifications 65 have been shown to decrease serum AMH levels in patients with PCOS.…”
Section: Resultsmentioning
confidence: 99%
“…Metformin administration, [60][61][62][63] bariatric surgery, 64 and lifestyle modifications 65 have been shown to decrease serum AMH levels in patients with PCOS.…”
Section: Resultsmentioning
confidence: 99%
“…Obesity can lead to insulin resistance that exacerbates the symptoms of PCOS, in that the adverse effects of PCOS are more prevalent in obese women ( 61 ). Additionally, insulin resistance contributes to ovulation disorders and abnormal endometrial structure ( 62 , 63 ). As discussed above, factors such as metabolic disorders and hormonal imbalancement still play a role in the effects of diet on infertility, suggesting that the use of causal language is necessary when discussing the link between diet and infertility.…”
Section: Discussionmentioning
confidence: 99%
“…13,14 Notably, several reports suggest that majority of infertility cases due to ovulation disorders may be preventable through modi cations of diet and lifestyle, particularly by increased consumption of either proteins or low-glycemic index carbohydrates. [14][15][16] A systematic review by Shang et al suggests that positive dietary changes improve fertility outcomes in women with polycystic ovary syndrome (PCOS) 17 , one of the common causes of female infertility, affecting 6-12% of US women of reproductive age 18 . They reported that the clinical pregnancy rate increased, especially with the Mediterranean and low-carbohydrate diets, and was shown to further improve with a longer diet treatment.…”
Section: Discussionmentioning
confidence: 99%